KEPUTUSAN TIDAK MEMILIKI ANAK DALAM PERSPEKTIF TEORI KONSTRUKSI SOSIAL DI INDONESIA - Nada Salsabila Isafitri; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
This study aims to elucidate the phenomenon of the decision not to have children through the perspective of social construction theory. Employing a Literature Review method, the research analyzes factors influencing couples’ decisions not to have children, as well as its impacts on personal levels, marital relationships, and the surrounding environment. The research methodology involves a literature review encompassing readings, previous research articles, and relevant books on the topic of the decision not to have children and social construction theory. Analysis is conducted using Peter L. Berger’s Social Construction Theory as the theoretical framework. The results highlight various factors contributing to the decision not to have children, including economic burdens, changes in female workforce participation, and potentially distressing childhood experiences. Additionally, the study indicates that social norms and meaning construction play significant roles in shaping individuals’ views on having or not having children. In the Indonesian context, different cultural norms and social interactions influence individuals’ understanding and decisions regarding this matter. Thus, this research provides deeper insights into the social and cultural dynamics surrounding the phenomenon of the decision not to have children in Indonesia.